ON CONTRADICTIONS IN EVALUATION AND CHARACTERISTICS OF DOCUMENTS OF THE RUSSIAN PROSECUTOR GENERAL OFFICE AND OTHER LAW ENFORCEMENT BODIES - M. A. Gavrilov (Russian Journal of Economics and Law, 2011)
The article views the contradictions found in legal and methodological documents of the Russian Prosecutor General Office and concerning the List of corruptive crimes. The author suggests, in order to unify the law enforcement and efficiency evaluation of corruption counteraction, to set such a list in the Federal Law On corruption counteraction.